Turnout in State Gubernatorial Primary Elections, 1950-1982 - Jewell, Malcolm ([Verlag nicht ermittelbar], 1985)
This collection consists of voting turnout statistics for every contested gubernatorial primary election in 47 states from 1950 through 1982. Information is also included for states holding elections for four-year gubernatorial terms during 1946 and 1948. Data are not available for Delaware, Indiana, and New York, since primaries had not been adopted yet in these states. Information is provided on the number of candidates in each primary, total vote for the winner, and total vote in the party primary. In addition to raw vote totals, several derived variables are also included. A "normal" Democratic and Republican vote statistic, based on the average number of votes cast for the party's candidates for governor, United States senator, and United States congressman, is calculated for each year in each state as a means of comparing the total party primary vote with its vote in the general election. Furthermore, the study includes an adjusted voting age estimate for 11 southern states. That estimate is a ratio of the total number of Blacks of voting age to the total number of Black registered voters and is designed to control for the impact of discrimination on voter turnout prior to 1970.